The COVID-19 & Socio-Economic Development of Pakistan from the Perspective of Distributive Justice - Kalim Ullah; Aqeela Asif; Syed Adnan Bukhari, (ASIAN Journal of International Peace & Security (AJIPS), 2024)
The COVID-19 pandemic's global impact exposed the vulnerabilities of the neoliberal economic model, particularly in developing nations like Pakistan. This paper investigates how the pandemic exacerbated existing inequalities in Pakistan, focusing on how the limitations of neoliberalism were laid bare. Through a critical analysis of the reports from international organizations, academic journals, and news articles, the research explores the severe impact of COVID-19 on Pakistan. Stringent lockdowns led to massive job losses, especially in the informal sector with weak social safety nets. This resulted in a significant decline in socio-economic development and pushed millions back into poverty. The crisis highlighted the stark disparities in healthcare access and economic resilience between developed and developing regions. In response to these limitations, the paper argues for a shift away from unfettered globalization and explores the concept of "relative autarky" as a potential framework. This model would empower states to regulate markets and prioritize social welfare while maintaining international cooperation. Ultimately, the paper concludes that the pandemic necessitates a critical reevaluation of economic models. By adopting frameworks that prioritize distributive justice and international collaboration, Pakistan and other developing nations can build a more equitable and resilient future.